Contra deltagb-Continuous Functions in Topological Spaces (European Journal of Pure and Applied Mathematics, 2017)
In this paper,the notion of gb-open sets in topological spaces is ap-plied to study a new class of functions called contra gb- continuousfunctions as a new generalization of contra continuity and obtain theircharacterizations and properties.
Keywords: deltagb-open; deltagb-closed; deltagb-connected; contra deltagb-continuous; deltagb- continuous.